IMPLIKASI KKN NUSANTARA KOLABORASI ANTAR PERGURUAN TINGGI KEAGAMAAN DALAM MENJAGA MUTU TOLERANSI DI DUNIA PENDIDIKAN - dewa_permana21, I Dewa Gede Darma Permana (Jurnal Penjaminan Mutu, 2024)
The year 2022 has been proclaimed as the year of tolerance by the Ministry of Religious Affairs of the Republic of Indonesia. To support this discourse, there is a new cooperation program carried out by religious universities called KKN Nusantara Collaboration. This collaboration program is carried out by I Gusti Bagus Sugriwa State Hindu University Denpasar, Syarif Hidayatullah State Islamic University Jakarta, and Walisongo State Islamic University Semarang to provide space for students to serve the community by promoting tolerance. Referring to this collaboration, researchers have an interest in examining the implications of the 'KKN Nusantara Collaboration' program. This study formulates three problem formulations, namely the urgency of tolerance in Indonesian education, the form of work programs in the 'KKN Nusantara Collaboration' and finally the implications in maintaining the quality of tolerance in education. Choosing qualitative research with a phenomenological approach, as well as collecting data through literature studies and having Miles and Huberman Interactive data analysis techniques, this study shows the results of the content and discussion that, the 'KKN Nusantara Collaboration' program is the answer to the urgency of cultivating tolerance in Indonesian education. The 'KKN Nusantara Collaboration' program can be made in the form of several activities, including the introduction of holy places, preservation of regional culture, socialization of religious moderation, and celebration of Independence Day. All of these activities have a positive impact in maintaining the quality of tolerance.